Correlation of Eye-Foot Coordination with Shooting Results in Soccer - Jud (S&Co Publishing, 2026)
This study aims to determine the correlation between foot-eye coordination and shooting results in soccer games. This study uses a quantitative method with a correlational approach. The population in this study were all 84 students of class VIII of SMP Negeri 10 Kendari, consisting of 39 girls and 45 boys. The sample in this study was 45 people taken using a purposive sampling technique where the sample in this study was taken based on consideration of male gender. The instrument used to measure foot-eye coordination was the soccer wall volley test, while the instrument used to measure shooting accuracy was the shooting test. Based on the statistical analysis of the correlation test using the SPSS 25 application, the coefficient relationship between the foot-eye coordination variable and shooting accuracy was positive, where the calculated r value was 0.516 at a significance level of 0.005 <0.05 with a coefficient of determination of 0.266 or 26.6%. This means that there is a significant relationship between foot-eye coordination and shooting results in soccer games. If entered on the correlation map, the relationship between the two variables is in the moderate category. Foot-eye coordination contributes 26.6% to shooting results. This study concludes that foot-eye coordination has a significant relationship with shooting results in soccer.